Laparoscopic Resection of Cholecystocolic Fistula and Subtotal Cholecystectomy by Tri-Staple in a Type V Mirizzi Syndrome - Fahri Yetişir; Akgün Ebru Şarer; Hasan Zafer Acar; Omer Parlak; Basar Basaran; Omer Yazıcıoğlu (Case Reports in Hepatology)
The Mirizzi syndrome (MS) is an impacted stone in the cystic duct or Hartmann’s pouch that mechanically obstructs the common bile duct (CBD). We would like to report laparoscopic subtotal cholecystectomy (SC) and resection of cholecystocolic fistula by the help of Tri-Staple™ in a case with type V MS and cholecystocolic fistula, for first time in the literature. A 24-year-old man was admitted to emergency department with the complaint of abdominal pain, intermittent fever, jaundice, and diarrhea. Two months ago with the same complaint, ERCP was performed. Laparoscopic resection of cholecystocolic fistula and subtotal cholecystectomy were performed by the help of Tri-Staple. At the eight-month follow-up, he was symptom-free with normal liver function tests. In a patient with type V MS and cholecystocolic fistula, laparoscopic resection of cholecystocolic fistula and SC can be performed by using Tri-Staple safely.